Axial crush performance of polymer-aluminium alloy hybrid foam filled tubes - Duarte, Isabel (2019)
The paper presents the findings of a pioneering study investigating the newly developed polymer-aluminium alloy hybrid foam as fillers of thin-walled square tubes made of aluminium alloy, as an alternative to the conventional closed-cell aluminium foams. The hybrid foam filled structures were prepared by infiltrating an aluminium alloy open-cell foam with silicone or epoxy inside the thin-walled tubes. Quasi-static and dynamic crush compressive response, deformation and failure modes and energy absorption characteristics of the hybrid foam filled structures were evaluated and compared to the empty tubes and tubes filled with conventional aluminium alloy open-cell foam (with voids). Results show that the deformation of the square thin-walled is improved due to the open-cell foam filler. It stabilises the tube and prevents the unstable global bending mode or a mixed buckling mode that is considered as an inefficient mode from the crashworthiness point of view. The deformation of the hybrid foam filled tubes was accompanied with a progressive folding mode. It was also observed that the polymer fillers caused the rupture of the outer tube at the corners, which results in higher energy apportion but might limit their application. However, it was found that the most efficient hybrid foam filled structures studied, in terms of crashworthiness, were the tubes filled with the epoxy-aluminium alloy hybrid foam. An increase of 610% and 300% in energy absorption and 78% and 51% in specific energy absorption of hybrid foam filled structures with length of 25 mm and 50 mm in comparison to the empty tubes (at strain of 0.7) was noted, respectively.